(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
In my study I provide an overview of professional literature about the positive and negative effects of formal and non-formal adult learning on mental well-being. I analyze for instance the joy of learning, the increase of self-confidence, the sense of success, the wider intellectual horizon and the more positive attitude to life out of some positive learning effects. As for the negative learning effects I write mostly about the role of conflicts, multilayer commitments, anxiety and the adequacy of pressure.